E-GOVERNMENT DAN PEMASARAN KOTA - Meyzi Heriyanto (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2003)
In Indonesia, Topic of e-government become popular after attributed todecentralization. Decentralization is conducive to develop e-government having potency torealize selling the city. Selling the city covers marketing of image, attraction, infrastructure,and its resident. This article is trying to depict the relation between e-government and sellingthe city.